The New Anatomy of Neuroimmunology - Solaro, Claudio; Barratt, David; Vaccarezza, Mauro (mdpi, 2022)
In the past few years, a renowned interest in the interplay between the immune system and central nervous systems (CNS) has sparked a wealth of new experimental studies. Two recent publications in Science shed new light on the “resident” immune cell populations in the CNS and their functions in homeostasis and pathological status, with potential implications in understanding CNS disease mechanisms and in designing new “intelligent” therapies